2022
DOI: 10.3389/fnut.2022.847966
|View full text |Cite
|
Sign up to set email alerts
|

Gallnut Tannic Acid Exerts Anti-stress Effects on Stress-Induced Inflammatory Response, Dysbiotic Gut Microbiota, and Alterations of Serum Metabolic Profile in Beagle Dogs

Abstract: Stress exposure is a potential threat to humans who live or work in extreme environments, often leading to oxidative stress, inflammatory response, intestinal dysbiosis, and metabolic disorders. Gallnut tannic acid (TA), a naturally occurring polyphenolic compound, has become a compelling source due to its favorable anti-diarrheal, anti-oxidative, anti-inflammatory, and anti-microbial activities. Thus, this study aimed to evaluate the anti-stress effects of gallnut TA on the stress-induced inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…The metabolomic analysis revealed metabolic profile alternations in response to the gut microbiota reprogrammed by a qingchang wenzhong decoction (QCWZD), especially enhanced Trp metabolism [ 54 ]. Gallnut tannic acid and the zingiber officinale–panax ginseng herb pair also stimulated the growth of the beneficial bacteria and suppressed the growth of the pathogenic bacteria [ 55 , 56 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…The metabolomic analysis revealed metabolic profile alternations in response to the gut microbiota reprogrammed by a qingchang wenzhong decoction (QCWZD), especially enhanced Trp metabolism [ 54 ]. Gallnut tannic acid and the zingiber officinale–panax ginseng herb pair also stimulated the growth of the beneficial bacteria and suppressed the growth of the pathogenic bacteria [ 55 , 56 ].…”
Section: Trp Metabolism In Gut Microbiotamentioning
confidence: 99%
“…In addition, the fecal and serum metabolomic analyses revealed that GA markedly reversed the abnormalities of nutrient metabolism caused by stress [ 32 ]. Tannic acid extracted from gallnut (a widely used traditional medicine in China) inhibited the secretion of serum stress hormones (i.e., COR, GC, and ACTH) and the expression of heat shock protein 70 to protect dogs from stress-induced oxidative damage and inflammatory response [ 106 ]. Dietary supplementation with pomegranate peel extract (PPE) had a positive impact on the antioxidant status in dogs, improving indices of erythrocytic antioxidants, namely, reducing glutathione, catalase, glutathione peroxidase, and glutathione S-transferase, together with a reduction in lipid peroxidation [ 148 ].…”
Section: Dietary Strategies For Relieving Stress In Petsmentioning
confidence: 99%
“…Gut microbiota contribute to the host’s metabolism and the regulation of the immune system, thus significantly affecting the host’s physiological functions [ 57 ]. We found a high level of serum cholic acid and rifamycin S in the AMPs group.…”
Section: Discussionmentioning
confidence: 99%